Capsaicin and piperine can overcome multidrug resistance in cancer cells to doxorubicin - Li, Hanmei; Krstin, Sonja; Wang, Shihui; Wink, Michael (Molecules, 2018)
Background: Multidrug resistance (MDR) can develop in cancer cells after treatment with anticancer drugs, mainly due to the overexpression of the ATP-binding cassette (ABC) transporters. We analyzed the ability of two pungent-tasting alkaloids—capsaicin and piperine from Capsicum frutescens and Piper nigrum, respectively—to reverse multidrug resistance in the cancer cell lines Caco-2 and CEM/ADR 5000, which overexpress P-glycoprotein (P-gp) and other ABC transporters. Methods: The MTT assay was first used to determine the cytotoxicity of doxorubicin, the alkaloids, and digitonin alone, and then their combinations. Furthermore, rhodamine (Rho) 123 and calcein-AM were used to detect the effects of alkaloids on the activity of P-gp. Results: Capsaicin and piperine synergistically enhanced the cytotoxicity of doxorubicin in Caco-2 and CEM/ADR 5000 cells. Furthermore, capsaicin and piperine increased the intracellular accumulation of the fluorescent P-glycoprotein (P-gp) substrates rhodamine and calcein and inhibited their efflux from the MDR cell lines. Conclusion: Our study has demonstrated that capsaicin and piperine are P-gp substrates and have potential chemosensitizing activity, which might be interesting for the development of novel modulators of multidrug resistance.
Gesehen am 30.07.2018